Improving cork polymer composites for the automotive industry - Campos, António (2023)
[Excerpt] The pressure imposed by legislations and treaties to adopt more sustainable and eco-friendly alternative materials is rising. Therefore, the use of cork-polymer composites (CPC) in the automotive industry could bridge the difficulties they have complying with the environmental laws and the need of giving a second life to the cork industrial wastes. From the cork processing, residues are generated, also called cork subproducts, with granulometries that wouldn’t be possible to use in other cork typical applications. With the purpose of implementing a circular economy model and reduce the waste that would be generated in normal conditions by burning or by throwing the cork residues in a landfield, the investigation and the development of new products involving these residues are taking place. [...]